Opportunities and challenges of macrogenetic studies - Leigh, Deborah M; van Rees, Charles B; Millette, Katie L; Breed, Martin F; Schmidt, Chloé; Bertola, Laura D; Hand, Brian K; Hunter, Margaret E; Jensen, Evelyn L; Kershaw, Francine; Liggins, Libby; Luikart, Gordon; et al. (Nature reviews. Genetics, 2021)
The rapidly emerging field of macrogenetics focuses on analysing publicly accessible genetic datasets from thousands of species to explore large-scale patterns and predictors of intraspecific genetic variation. Facilitated by advances in evolutionary biology, technology, data infrastructure, statistics and open science, macrogenetics addresses core evolutionary hypotheses (such as disentangling environmental and life-history effects on genetic variation) with a global focus. Yet, there are important, often overlooked, limitations to this approach and best practices need to be considered and adopted if macrogenetics is to continue its exciting trajectory and reach its full potential in fields such as biodiversity monitoring and conservation. Here, we review the history of this rapidly growing field, highlight knowledge gaps and future directions, and provide guidelines for further research.